“Cool courage should always mark me”: John Wilkes and Duelling - Sainsbury, John (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1996)
AbstractThe duelling activity of John Wilkes, the eighteenth-century English radical, has not received much attention from historians. Yet it tells us a lot about his career and the responses that it evoked from the public at large. Through allegiance to the honour code, Wilkes self-consciously sought to identify with the hegemonic aristocratic culture, an insight which renders problematic his frequent depiction as the champion of a bourgeois style of politics. At the same time, his duelling helped to elicit popular support because it defined a manly persona which could be contrasted with the effeteness of his political enemies, especially those who had allegedly betrayed England's patriotic interests in the country's struggle with France. Significantly, Wilkes's duelling career ended once he found sanctuary in London's civic arena, where the honour code was discounted in favour of demonstrations of political heroism that were not potentially fatal.